2016
DOI: 10.1016/j.bbi.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Microglial P2Y12 receptors regulate microglial activation and surveillance during neuropathic pain

Abstract: Microglial cells are critical in the pathogenesis of neuropathic pain and several microglial receptors have been proposed to mediate this process. Of these receptors, the P2Y12 receptor is a unique purinergic receptor that is exclusively expressed by microglia in the central nervous system (CNS). In this study, we set forth to investigate the role of P2Y12 receptors in microglial electrophysiological and morphological (static and dynamic) activation during spinal nerve transection (SNT)-induced neuropathic pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 70 publications
8
103
0
Order By: Relevance
“…Whether the alteration in the process morphology of SDH microglia contributes to subsequent proliferation and neuropathic pain induction remains unknown. 4) Given that PNI-induced pain hypersensitivity is blunted in mice lacking a molecule (P2Y12 receptor or transmembrane protein 16F) that regulates the shape of microglial processes, 29,30) it is possible that the first morphological change in SDH microglia by PNI may also have a role in subsequent microgliosis and neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the alteration in the process morphology of SDH microglia contributes to subsequent proliferation and neuropathic pain induction remains unknown. 4) Given that PNI-induced pain hypersensitivity is blunted in mice lacking a molecule (P2Y12 receptor or transmembrane protein 16F) that regulates the shape of microglial processes, 29,30) it is possible that the first morphological change in SDH microglia by PNI may also have a role in subsequent microgliosis and neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain is a chronic pain caused by a lesion or disease of the somatosensory nervous system and characterized by hyperalgesia and allodynia [1,2]. It is an unpleasant sensory consequence of neuronal activities in specific nociceptive pathways that is triggered by noxious stimuli, inflammation, or damage to the nervous system [3].…”
Section: Introductionmentioning
confidence: 99%
“…P2Y12R plays a vital role in microglia activation, as they act as the primary site at which nucleotides act to induce microglial chemotaxis in response to local CNS injury (Haynes et al, 2006, De Simone et al, 2010). It has been shown that enhanced P2Y12R-mediated purinergic signaling was responsible for microglial activation and the resultant increase in voltage-activated potassium currents in hippocampal microglia following status epilepticus (Avignone et al, 2008) and in spinal microglia following peripheral nerve injury (Gu et al, 2015). P2Y12R activation has also been shown to mediate microglial process extension and convergence towards dendrites following neuronal hyperactivity (Eyo et al, 2014, Eyo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%